STRATEGI PENERAPAN EKO-DRAINASE DI KAWASAN GAMPOENG KEURAMAT BANDA ACEH - Munzirwan Habibi; Eldina Fatimah; Azmeri Azmeri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: Generally in Gampong Keuramat region still uses the conventional drainage concept. Along with the rapid development that occurred in Banda Aceh, especially at Gampong Keuramat after the Tsunami in 2004, resulting in the decrease of vacant land that could be used to absorb water into the soil. This matter causes the water system distruption and take affect toward urban flood control. Concerns with these problems it is required to control the peak flows through the structural efforts and to apply environment drainage (eco-drainage). The purpose of this study is to analyze flow rates (Qpasca) drainage system by using the concept of system eco-drainage and formulate strategies to implement the concept of system eco-drainase by using SWOT analysis. The method of data collection is by using secondary data and primary data. The data were processed statistically descriptive and SWOT analysis. From the observations, the existing condition and the road condition and channels in Gampoeng Kueramat need to be maintained and improved. The calculations show that, th service zone I until V occurred the reduction of average discharge 48.948%, 58.412%, 43.468%, 72.034% and 72.919%. The result from SWOT analysis is obtained some strategies: (1) use the support of society in an effort to overcome the problems of drainage as a puddle with drainage planning sustainable or eco-drainage, (2) to convince the provincial government to support programs / activities of eco-drainage with the allocation of appropriate funds targeted to address the flooding problems, to maintain the continuity of the water and drainage system in Gampoeng Keuramat, (3) use the support of society in land use to make infiltration wells and expand land infiltration in the society environment, and (4) to disseminate to the public for a change paradigm in dealing with the flood of effort to keep the water from settlements with trying to keep the water as long as possible and utilize as much water as possible is called the concept of